Use the quadratic formula to find the solutions. − b ± √ b 2 − 4 ( a c ) 2 a – b ± b 2 – 4 ( a c ) 2 a Substitute the values a = 1 a = 1 , b = 0 b = 0 , and c = − 9 c = – 9 into the quadratic formula and solve for x x . 0 ± √ 0 2 − 4 ⋅ ( 1 ⋅ − 9 ) 2 ⋅ 1 0 ± 0 2 – 4 ⋅ ( 1 ⋅ – 9 ) 2 ⋅ 1 Simplify. Tap for more steps… x = ± 3 x = ± 3 The final answer is the combination of both solutions. x = 3 , − 3

## Answers ( )

Use the quadratic formula to find the solutions.

−

b

±

√

b

2

−

4

(

a

c

)

2

a

–

b

±

b

2

–

4

(

a

c

)

2

a

Substitute the values

a

=

1

a

=

1

,

b

=

0

b

=

0

, and

c

=

−

9

c

=

–

9

into the quadratic formula and solve for

x

x

.

0

±

√

0

2

−

4

⋅

(

1

⋅

−

9

)

2

⋅

1

0

±

0

2

–

4

⋅

(

1

⋅

–

9

)

2

⋅

1

Simplify.

Tap for more steps…

x

=

±

3

x

=

±

3

The final answer is the combination of both solutions.

x

=

3

,

−

3

Answer:x=3

Step-by-step explanation:Step 1: Subtract 9 from both sides.

x2−6x+9−9=0−9

x2−6x=−9

Step 2: The coefficient of -6x is -6. Let b=-6.

Then we need to add (b/2)^2=9 to both sides to complete the square.

Add 9 to both sides.

x2−6x+9=−9+9

x2−6x+9=0

Step 3: Factor left side.

(x−3)2=0

Step 4: Take square root.

x−3=±√0

Step 5: Add 3 to both sides.

x−3+3=3±√0

x=3±√0

x=3+0 or x=3−0

x=3